2013
DOI: 10.1007/s10443-013-9322-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Interface Behavior of Balanced and Unbalanced E-Glass/Polyester Woven Fabric Composite Laminates

Abstract: The aim of this work is to study the influence of weave structure on the crack growth behavior of thick E-glass/polyester woven fabric composites laminates. Two different types of laminates were fabricated: (i) balanced: plain weave (taffetas T)/chopped strand mat weave (M) [T/M] 6 and (ii) unbalanced: 4-hardness satin weave (S)/chopped strand mat weave [S/M] 7 . In order to accurately predict damage criticality in such structures, mixed mode fracture toughness data is required. So, the experiments were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In this FPZ, the material at the crack tip commences to nonlinearly behavior induced by some phenomena such as fiber bridging, micro-cracking, and plastic transformation of the material that toughen the material at the crack tip. These mechanisms absorb the energy of the loaded structure, which prevents catastrophic failure and delays crack growth [57,58,95]. Substantial as the FPZ is in the fracture phenomenon, it was disregarded in the primary mixed-mode loading criteria.…”
Section: Development Of Isedm Criterion With the Midpointmentioning
confidence: 99%
See 1 more Smart Citation
“…In this FPZ, the material at the crack tip commences to nonlinearly behavior induced by some phenomena such as fiber bridging, micro-cracking, and plastic transformation of the material that toughen the material at the crack tip. These mechanisms absorb the energy of the loaded structure, which prevents catastrophic failure and delays crack growth [57,58,95]. Substantial as the FPZ is in the fracture phenomenon, it was disregarded in the primary mixed-mode loading criteria.…”
Section: Development Of Isedm Criterion With the Midpointmentioning
confidence: 99%
“…Recently, it is proven that the fracture process zone (FPZ) significantly influences the fracture process of composite materials [48][49][50][51][52][53][54]. In the FPZ, several mechanisms such as the nucleation of micro-cracks cause the dissipation of energy and prevent catastrophic failure [55][56][57][58][59]. The effects of the FPZ, where micro-cracks nucleate and propagate, have been studied and a criterion derived based on dissipated energy in the FPZ [60].…”
Section: Introductionmentioning
confidence: 99%
“…Plentiful researches about the effects of weave structure on mechanical properties have been reported. Triki et al [15] found that the mechanical properties of plain weave/chopped strand mat weave are better than that of 4-hardness satin weave/chopped strand mat weave for the thick E-glass/polyester woven fabric composites laminates. Foroutan et al [16] investigated the shear and tensile behaviors of carbon/epoxy composites and Carbon/BMI composites with plain weave, 2 × 2 twill weave and 8-harness satin weave, and then discovered that the shear behaviors are more rate-dependent than their tensile behaviors.…”
Section: Introductionmentioning
confidence: 98%
“…Triki [7] in his research on the influence of the fabric structure on the crack growth behavior of glass/polyester composite laminates, using fracture toughness tests, was able to determine that the balanced interface is more resistant to delamination than the balanced interface. Unbalanced interface.…”
Section: Introductionmentioning
confidence: 99%